Fitting algorithm for interferometric spectrum of fiber Fabry-Perot cavity acoustic sensors. Issue 3 (August 2019) - Yu, Changkun; Cheng, Jin; Tian, Yangmeng; Zou, Xiaoping
Abstract: Fiber Fabry-Perot cavity acoustic sensors have been widely used in some fields recently due to its advantages such as high sensitivity, resistance to electromagnetic interference, etc. In order to control the performance of the sensors, it is necessary to precisely adjust the cavity length. In order to obtain the cavity length efficiently and accurately, a fitting algorithm for interference spectrum is proposed in this paper. The base of the algorithm is the principle of light interference and the key of the algorithm is to find the peaks and valleys of the interference spectrum. Experimental results show that the algorithm has a high fitting degree.